Basilica - William D. Montalbano (U.S.A Jove Books, 1998)
"An action novel wrapped around a murderous intrigue, with a revolutionary Pope, a wayward monk and an insane killer sharing the heart of the story. There's a combination of human warmth and sheer terror that makes Basilica impossible to put down." --John Sandford"The absolute best...a literally thrilling achievement." --Pete Hamill
Keywords: Mystery/Suspense -- Mystery/Suspense